Correlation of Fibrinogen Level with PELOD-2 Score As A Predictive Factor For Mortality in Pediatric Sepsis - Susanti, Dia Tri; Yanni, Gema Nazri; Saing, Johannes H.; Mutiara, Erna; Lubis, Aridamuriany D.; Siregar, Olga R. (CoinReads Media Prima, 2023)
Introduction: Fibrinogen is a prognostic biomarker in septic children, lower fibrinogen levels are closely related to higher risk of death. Organ dysfunction was diagnosed based on PELOD-2 score. The aim of this study was to determine the corelation between fibrinogen levels and PELOD-2 score as a predictor of mortality in pediatric patient with sepsis treated in the PICU and HCU at H. Adam Malik General Hospital. Method: A cross-sectional study of pediatric patients with sepsis treated in the PICU and HCU H. Adam Malik General Hospital, Medan. Correlation of fibrinogen levels with PELOD-2 scores was seen on day I and day III of treatment in patient aged 1 month to 18 years with a hospital stay of at least 72 hours and were analyzed using the Spearman test and the relationship between fibrinogen and mortality was analyzed using the Mann-Whitney test. Results: 50 subjects were recruited in this study, fibrinogen levels had no correlation with PELOD-2 score day I (p = 0,074, r = -0,225) and with PELOD-2 score days III (p = 0,110, r = -0,229) and with mortality (p = 0,160). Conclusion: Fibrinogen levels were not correlate with PELOD-2 score as a predictive factor for mortality in septic children.